Burnout syndrome and the quality of life of patients with diabetes mellitus and hypertension - Vesna Krstović Spremo; Sanja Marić; Ljiljana Kulić (Биомедицинска истраживања, 2022)
Introduction: The World Health Organization (WHO) defines burnout syndrome as a condition caused by chronic stress at work, which may be associated with the onset and worsening of psychosomatic illnesses and the quality of life of sufferers. The aim of the work was to determine the prevalence of burnout syndrome in the population of people with leading, chronic, massive, non-communicable diseases, type 2 diabetes and arterial hypertension, while assessing the impact of this syndrome on the quality of life of the subjects. Methods: The research was conducted as a cross-sectional study from March 2019 until October 2019 on a randomized sample of 92 patients with type 2 diabetes and 99 patients with hypertension from two Health Centres in East Sarajevo. A special criterion for inclusion in the research was that the respondents were employed and that their age did not exceed 65 years. The research instrument was a general questionnaire, the WHO questionnaire on burnout syndrome, as well as the WHO SF-36 questionnaire on the quality of life, and statistical data processing was done in the SPSS program version 19.0. The significance of the difference was tested by the χ2 test, and the existence of burnout syndrome was defined according to the WHO questionnaire. Results: In subjects with diabetes, burnout syndrome was present in 52.8% (mildly expressed in 15.2% of the subjects, candidate for burnout syndrome in 19.6% of the subjects, burnout syndrome was present in 17.4%, while in one subject burnout syndrome that endangers health was found) and in subjects with hypertension, burnout syndrome was found in 32% of the subjects. Burnout syndrome was more present in subjects with diabetes than in subjects with hypertension. The difference was statistically significant (χ2 = 8.42; p = 0.003). Subjects with diabetes were significantly more depressed and discouraged than subjects in the group with hypertension (χ2 = 16.14; p < 0.01). The subjects with diabetes had significantly more difficulty in performing their job than those with hypertension during the past four weeks (χ2 = 13.098; p = 0.011). Conclusion: There is a significant frequency of burnout syndrome in patients with diabetes, but also in patients with hypertension. The existence of cause-and-effect relationships significantly affects the quality of life of patients and their ability to work.
Keywords: burnout syndrome; diabetes; hypertension; quality of life